Techno-economic analysis of the distribution system with integration of distributed generators and electric vehicles - Golla, Naresh Kumar; Dharavat, Nagaraju; Sudabattula, Suresh Kumar; Velamuri, Suresh; Kantipudi, M. V. V. Prasad; Kotb, Hossam; Shouran, Mokhtar; Alenezi, Mohammed (Frontiers in Energy Research, 2023)
Electric vehicles (EVs) have become a feasible alternative to conventional vehicles due to their technical and environmental benefits. The rapid penetration of EVs might cause a significant impact on the distribution system (DS) due to the adverse effects of charging the EVs and grid integration technologies. In order to compensate for an additional EV load to the existing load demand on the DS, the distributed generators (DGs) are integrated into the grid system. Due to the stochastic nature of the DGs and EV load, the integration of DGs alone with the DS can minimize the power losses and increase the voltage level but not to the extent that might not improve the system stability. Here, the EV that acts as a load in the grid-to-vehicle (G2V) mode during charging can act as an energy source with its bidirectional mode of operation as vehicle-to-grid (V2G) while in the discharging mode. V2G is a novel resource for energy storage and provision of high and low regulations. The article proposes a smart charging model of EVs, estimates the off-load and peak load times over a period of time, and allocates charging and discharging based on the constraints of the state of charge (SoC), power, and intermittent load demand. A standardized IEEE 33-node DS integrated with an EV charging station (EVCS) and DGs is used to reduce the losses and improve the voltage profile of the proposed system. Simulation results are carried out for various possible cases to assess the effective utilization of V2G for stable operation of the DS. The cost–benefit analysis (CBA) is also determined for the G2V and V2G modes of operation for a 24-h horizon.